الإشاعة : بحث انثروبولوجي في مدينة الصدر بأمانة بغداد - جميل احمد, محمد (Al-Adab Journal, 2018)
The research aims at revealing the cultural and psychological dimensions of the rumor and its impact in societies in general and in the community in particular. The rumor of topics of anthropological dimension, social and psychological, which is a clear influence in the life of society through the interaction that occurs in different formats, which makes members of the community live in conditions to a certain extent with the style of rumor used by each culture and then vary from one community to another according to Awareness and Response to Some Rumors For example, rumor in western society differs from that in Arab or Eastern society and differs in urban society from that of rural society. And employs rumor for different purposes to achieve some goals aimed at winning certain interests at a specific time and then rumor to explain some of the ideas and beliefs that correspond with the promoters of rumors whether the government or the media or the people or some people, especially when the community passes at certain times allowing To create new trends commensurate with the magnitude of this crisis, especially in the wars and deteriorating economic conditions and the social situation and the most common rumor is the weapon of the psychological wars. And has a significant impact in societies, especially in traditional societies of low awareness and low educational level, which means that rumor with different dimensions can be directed to the community in a positive or negative according to the strength of rumors and promoters and methods adopted.